Economics Data Analysis Device - Research on Enhancing the Efficiency of Economic Forecasting and Decision Making - Tang, Xianing; Peng, Junjie; Zhang, Xiuyuan; Liu, Yuhui (International Journal of Global Economics and Management, 2024)
This paper discusses an economics data analysis device, belonging to the technical field of data analysis devices, including a base plate and a universal wheel located at the bottom of the base plate, the top of the base plate is connected with a vertical column, the top of the vertical column is slidingly connected with a lifting column, the top of the lifting column is connected with an outer frame plate, the inner side wall of the outer frame plate is mounted with a display, the top of the base plate is mounted with an electric motor, the output end of the electric motor is connected with a screw rod, the screw rod of the motor is connected to a threaded rod, the outer side wall of the threaded rod is threadedly connected to a sleeve block, the outer side wall of the sleeve block is connected to a connecting block, and the outer side wall of the connecting block is slidingly connected to the outer side wall of the vertical column. The economics data analysis device, through the operation of the motor, the threaded rod is then rotated, and then through the use of the sleeve block and the connecting block, the lifting column is then moved, causing the height of the outer frame plate to change, so as to achieve the effect of facilitating the adjustment of the height of the display, and thus facilitating the observation and analysis of the data graph displayed on the display.